Analisis Persepsi Siswa Terhadap Penerapan Projek Penguatan Profil Pelajar Pancasila dan Rahmatan Lil Alamin (P5RA) - Haris Nursyah Arifin; Ismail, Syarof Nursyah (LPPM IAIN Sorong, 2025)
The implementation of the Merdeka Curriculum at Madrasah Aliyah Al-Amin Tabanan still faces challenges, particularly in terms of teachers adapting to the new paradigm. Some teachers struggle to adjust their teaching methods to align with the Merdeka Curriculum, especially regarding diagnostic assessments and project-based learning. One of the key characteristics of the Merdeka Curriculum is the P5RA Project. The evaluation results of the P5RA project implementation at MA Al-Amin Tabanan indicate that to enhance the effectiveness of the project, a more well-planned strategy is needed to minimize obstacles during its execution. This study employs a descriptive quantitative research method using surveys. The sample consists of 53 students from grades X and XI, with data collected through questionnaires, documentation, and interviews, followed by qualitative and quantitative data analysis. The research findings reveal that most students have an understanding of the objectives, benefits, and implementation process of the project. The execution of this project has had a positive impact on students, particularly in improving their understanding of various themes such as bullying, democracy, entrepreneurship, and sustainable lifestyles. Based on the research findings, recommendations for improving the implementation of the P5RA project include enhancing resources, providing teacher training, managing students' skills and interests, and ensuring continuous evaluation and feedback.